(untitled) - Jensen, Richard (Oxford, 2008)
Computational Intelligence and Feature Selection provides readers with the background and fundamental ideas behind Feature Selection (FS), with an emphasis on techniques based on rough and fuzzy sets. For readers who are less familiar with the subject, the book begins with an introduction to fuzzy set theory and fuzzy-rough set theory.
Keywords: Artificial intelligence,Set theory,Lý thuyết tập họp,Trí tuệ nhân tạo; Mathematical models,Phương pháp toán học